Haplotypes of the endothelial protein C receptor (EPCR) gene are not associated with severe malaria in Tanzania. (December 2015) - Hansson, Helle; Turner, Louise; Møller, Line; Wang, Christian; Minja, Daniel; Gesase, Samwel; Mmbando, Bruno; Bygbjerg, Ib; Theander, Thor; Lusingu, John; Alifrangis, Michael; Lavstsen, Thomas
Abstract Background Endothelial protein C receptor (EPCR) was recently identified as a key receptor forPlasmodium falciparum erythrocyte membrane protein 1 mediating sequestration ofP. falciparum -infected erythrocytes in patients suffering from severe malaria. Soluble EPCR (sEPCR) inhibits binding ofP. falciparum to EPCR in vitro and increased levels of sEPCR have been associated with the H3 haplotype of the EPCR encodingPROCR gene. It has been hypothesized that elevated sEPCR levels, possibly linked to thePROCR H3 genetic variant, may confer protection against severe forms of malaria. This study determined the frequencies ofPROCR haplotypes H1–4 and plasma levels of sEPCR in a Tanzanian study population to investigate a possible association with severe malaria. Methods Study participants were children under 5 years of age admitted at the Korogwe District Hospital (N = 143), and diagnosed as having severe malaria (N = 52; including cerebral malaria N = 17), uncomplicated malaria (N = 24), or an infection other than malaria (N = 67). In addition, blood samples from 71 children living in nearby villages were included. The SNPs defining the haplotypes ofPROCR gene were determined by post-PCR ligation detection reaction-fluorescent microsphere assay. Results Individuals carrying at least one H3 allele had significantly higher levels of sEPCR than individuals with no H3 alleles (P < 0.001). No difference in the frequency of H3 was found between the non-malaria patients, malaria patients or the village population (P > 0.1). Plasma levels of sEPCR differed between these three groups, with higher sEPCR levels in the village population compared to the hospitalized patients (P < 0.001) and higher levels in malaria patients compared to non-malaria patients (P = 0.001). However, no differences were found in the distribution of H3 (P = 0.2) or levels of sEPCR (P = 0.8) between patients diagnosed with severe and uncomplicated malaria. Conclusion Frequencies of SNPs determiningPROCR haplotypes were in concordance with other African studies. ThePROCR H3 allele was associated with higher levels of sEPCR, confirming earlier findings, however, in this Tanzanian population; neitherPROCR haplotype nor level of sEPCR was associated with severe malaria, however, larger studies are needed to confirm these findings.